Pengaruh Komitmen Organisasi Terhadap Kinerja Manajerial Dengan Anggaran Sebagai Variabel Moderating - Riyanto Riyanto (ManBiz: Journal of Management and Business, 2022)
Performance measurement is a process of assessing the progress of work against the goals and objectives predetermined, performance measurement used to assess the achievements manajaer and units of the organization he leads. the concept of managing public sector organizations based on three main elements, namely: economy, efficiency, and effectiveness. This study will analyze the influence of the independent variable on the dependent variable, namely the Participation Effect budget and organizational commitment to managerial performance in Islamic hospital Jakarta Cempaka Putih. Results showed partial (according t test) effect on theorganizational commitmen with budgetary participation as moderating variable of managerial performance. Then according to the results of t test, the partial effect on the organization's commitment managerial performance in performing their tasks and responsibilities. In carrying out the duties and responsibilities as a manager, it takes a strong commitment to the organization. Test results F illustrates that the simultaneous participation of the budget and organizational commitment jointly influence on managerial performance. R Square Test results showed R2 values ​​shown in the table amounted to 0.690 means that the variable budgetary participation and organizational commitment, able to explain 69.0% of these variations on managerial performance variable (Y). Keyword: organizational commitment, managerial performance, participation budget